2014
DOI: 10.1093/schbul/sbu150
|View full text |Cite
|
Sign up to set email alerts
|

Evidence From Structural and Diffusion Tensor Imaging for Frontotemporal Deficits in Psychometric Schizotypy

Abstract: Background: Previous studies of nonclinical samples exhibiting schizotypal traits have provided support for the existence of a continuous distribution of psychotic symptoms in the general population. Few studies, however, have examined the neural correlates of psychometric schizotypy using structural and diffusion tensor imaging (DTI). Methods: Healthy volunteers between the ages of 18 and 68 were recruited from the community and assessed using the Schizotypal Personality Questionnaire and received structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 71 publications
5
39
1
2
Order By: Relevance
“…In a recent study with paranoid schizophrenia patients, however, Zierhut et al (2013) reported that neuronal alterations of both the prefrontal and temporal lobes synergistically contribute to the development of paranoid symptoms and cognitive dysfunction. Thus, the present findings (a) suggest that impaired attention switching is a "core" deficit of NegS and ParS, as it was found in both the dimensional and categorical analyses; (b) propose that working memory and set shifting are "first-rank" deficits in NegS (found both in dimensional and in categorical analyses) and "second-rank" deficits in ParS, probably due to prefrontal alterations evident only in individuals occupying the most extreme end of this schizotypal dimension; and (c) further support the disturbed frontotemporal connectivity found in SPD (Hazlett, Goldstein, & Kolaitis, 2012) and psychometric schizotypy (DeRosse et al, 2015), which seems to be mostly true for the ParS dimension.…”
Section: Discussionsupporting
confidence: 68%
“…In a recent study with paranoid schizophrenia patients, however, Zierhut et al (2013) reported that neuronal alterations of both the prefrontal and temporal lobes synergistically contribute to the development of paranoid symptoms and cognitive dysfunction. Thus, the present findings (a) suggest that impaired attention switching is a "core" deficit of NegS and ParS, as it was found in both the dimensional and categorical analyses; (b) propose that working memory and set shifting are "first-rank" deficits in NegS (found both in dimensional and in categorical analyses) and "second-rank" deficits in ParS, probably due to prefrontal alterations evident only in individuals occupying the most extreme end of this schizotypal dimension; and (c) further support the disturbed frontotemporal connectivity found in SPD (Hazlett, Goldstein, & Kolaitis, 2012) and psychometric schizotypy (DeRosse et al, 2015), which seems to be mostly true for the ParS dimension.…”
Section: Discussionsupporting
confidence: 68%
“…The pattern of stronger connectivity with increasing schizotypy scores may reflect a continuum of factors underlying schizophrenia spectrum traits, from low‐to‐medium expression to the clinical condition [Fornito et al, ]. Associations of stronger right‐hemispheric asymmetries in relation to schizotypy similarly extend pervious work showing greater right > left asymmetry in other schizophrenia spectrum populations [DeRosse et al, ; Hori et al, ; Mueller et al, ].…”
Section: Discussionmentioning
confidence: 66%
“…Evidence from previous neuroimaging studies has pointed to structural and functional brain alterations in relation to higher schizotypy scores [Ettinger et al, ]. Specifically, structural magnetic resonance imaging studies have shown that higher schizotypy is associated with reduced gray matter in frontotemporal areas [DeRosse et al, ; Ettinger et al, ; Wang et al, ; Wiebels et al, ], while there is also evidence of increased gray matter in posterior cingulate and precuneus [Modinos et al, ; Nenadic et al, ]. Functional magnetic resonance imaging studies have pointed to alterations in task‐related BOLD signal during performance of cognitive or motor tasks [Ettinger et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these two studies using current VBM methodology, identified medial and lateral prefrontal and anterior cingulate, as well as posterior cingulate and precuneus areas showing a relation to measures of attenuated positive symptoms. In addition, two most recent studies have identified brain structural effects in grey matter with reduced grey matter density in high schizotypy individuals (based on the SPQ) in the dorsolateral prefrontal and insular cortices (Wang et al, 2015), as well as reduced middle frontal grey and white matter, reduced inferior fronto-occipital fasciculus anisotropy, and greater fasciculus uncinatus asymmetry in high schizotypy (using SPQ) individuals (DeRosse et al, 2015).…”
Section: Introductionmentioning
confidence: 99%